Embezzlement in the Private Sector: Legal Challenges and Regulatory Gaps in Corporate Governance - Kiki Kristanto; Muhamad Adystia Sunggara; Mas Putra Zenno Januarsyah; Pita Permatasari; Vicko Taniady (Indonesian Journal of Criminal Law Studies, 2025)
This study critically examines the issue of embezzlement in the private sector, a form of white-collar crime that continues to pose significant threats to corporate integrity, investor trust, and economic stability. Despite its prevalence and damaging consequences, legal responses remain fragmented both at the level of national legislation and international legal harmonization. Using a normative legal method with statutory, conceptual, comparative, and futuristic approaches, this research systematically analyzes the underlying legal and institutional deficiencies and formulates reform-oriented recommendations. Drawing on statutes, case law, academic doctrines, and cross-jurisdictional practices, the study identifies key regulatory gaps: the absence of a consistent legal definition of private sector embezzlement, weak enforcement mechanisms, and insufficient corporate accountability provisions. Comparative insights from jurisdictions such as the United States, Germany, and Singapore highlight the effectiveness of integrated models combining criminal sanctions, internal compliance obligations, and external oversight. In light of these findings, the study proposes targeted reforms in Indonesian corporate law particularly to clarify corporate criminal liability, mandate real-time internal controls, and establish independent ethics committees. These proposals are intended to guide lawmakers, regulatory bodies, and corporate policymakers toward developing more effective enforcement mechanisms and corporate governance structures. Ultimately, the study underscores that embezzlement is not merely a legal infraction but a systemic governance failure requiring coordinated legal, institutional, and ethical responses across national and international levels.